2016
DOI: 10.1007/s00280-016-3220-6
|View full text |Cite
|
Sign up to set email alerts
|

First-dose and steady-state pharmacokinetics of orally administered crizotinib in children with solid tumors: a report on ADVL0912 from the Children’s Oncology Group Phase 1/Pilot Consortium

Abstract: Purpose Characterize the pharmacokinetics of oral crizotinib in children with cancer.MethodsSixty-four children with solid tumors or anaplastic large-cell lymphoma (ALCL) enrolled on a phase 1/2 trial of the ALK, MET and ROS1 inhibitor, crizotinib, had pharmacokinetic sampling after the first dose (n = 15) or at steady state (n = 49). Dose levels studied were 100, 130, 165, 215, 280 and 365 mg/m2/dose administered twice daily. Two capsule and two oral liquid formulations were used over the course of the trial.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…were comparable to those reported recently in children with solid tumors despite significant methodologic differences between both studies (for example, drug formulation and pharmacokinetic sampling strategy). 21 Our results demonstrating a decrease in p-AKT in PBMC after administration of dasatinib are interesting, although significant concern remains that dasatinib does not reach clinically effective concentrations in the CNS. 20,22 The longitudinal analysis of plasma HGF was performed based on the report that its expression was predictive of response to c-Met inhibition in HGG preclinical models.…”
Section: Discussionmentioning
confidence: 77%
“…were comparable to those reported recently in children with solid tumors despite significant methodologic differences between both studies (for example, drug formulation and pharmacokinetic sampling strategy). 21 Our results demonstrating a decrease in p-AKT in PBMC after administration of dasatinib are interesting, although significant concern remains that dasatinib does not reach clinically effective concentrations in the CNS. 20,22 The longitudinal analysis of plasma HGF was performed based on the report that its expression was predictive of response to c-Met inhibition in HGG preclinical models.…”
Section: Discussionmentioning
confidence: 77%
“…The pharmacokinetics of oral crizotinib in children is similar to that in adults. The COG consortium study in 79 children with refractory solid tumors or anaplastic large‐cell lymphoma found that crizotinib was well tolerated with a recommended single‐agent phase 2 dose of 280 mg/mg 2 twice daily …”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…The COG consortium study in 79 children with refractory solid tumors or anaplastic large-cell lymphoma found that crizotinib was well tolerated with a recommended single-agent phase 2 dose of 280 mg/mg 2 twice daily. 23,38,39 Notably, one of our patients received the drug via nasogastric tube due to incompliance, which nevertheless led to CR of the tumor. Unfortunately, assessment of the serum levels had not been performed in our cases.…”
Section: Second-generation Alk Inhibitors In Imtmentioning
confidence: 98%
“…), the mean C min in pediatric patients was 480 ng/mL, corresponding to a free drug concentration of 50 ng/mL. 18 The unbound drug concentration of 50 ng/mL exceeds the concentration of drug producing 50% inhibition of 10 ng/mL of crizotinib in ALCL cell lines. No relationships between exposure and efficacy have been established for crizotinib in adults with NSCLC nor pediatric patients with ALCL.…”
Section: Crizotinibmentioning
confidence: 92%